PENGARUH KOMPETENSI DAN MANAJEMEN PENGETAHUAN TERHADAP KINERJA PEGAWAI SUB BAGIAN ORGANISASI DAN KEPEGAWAIAN, BADAN PENGEMBANGAN SUMBER DAYA MANUSIA, KEMENTERIAN DALAM NEGERI MELALUI KEMAMPUAN BERKOLABORASI - Tubagus Arief Budiman; Imam Wibowo; Eddy Sanusi. S (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
This research aims to find out whether competency and knowledge management have a positive and significant effect on employee performance through the ability to collaborate in the Organization and Personnel Sub-Section, Human Resources Development Agency, Ministry of Home Affairs. This research method was carried out on employees of the Organization and Personnel Subdivision, Human Resources Development Agency, Ministry of Home Affairs. The data collection method used was by distributing closed questionnaires. In this research, the used a random sampling method. The data analysis model used a path analysis test. The results of this research indicate that collaboration ability cannot be an intervening variable between competence and employee performance nor between knowledge management and employee performance.